West Nile virus infectious replicon particles generated using a packaging-restricted cell line is a safe reporter system - Wei Li (Nature Portfolio, 2017)
Abstract West Nile virus (WNV) is a neurotropic pathogen which causes zoonotic disease in humans. Recently, there have been an increasing number of infected cases and there are no clinically approved vaccines or effective drugs to treat WNV infections in humans. The purpose of this study was to facilitate vaccine and antiviral drug discovery by developing a packaging cell line-restricted WNV infectious replicon particle system. We constructed a DNA-based WNV replicon lacking the C-prM-E coding region and replaced it with a GFP coding sequence. To produce WNV replicon particles, cell lines stably-expressing prM-E and C-prM-E were constructed. When the WNV replicon plasmid was co-transfected with a WNV C-expressing plasmid into the prM-E-expressing cell line or directly transfected the C-prM-E expressing cell line, the replicon particle was able to replicate, form green fluorescence foci, and exhibit cytopathic plaques similar to that induced by the wild type virus. The infectious capacity of the replicon particles was restricted to the packaging cell line as the replicons demonstrated only one round of infection in other permissive cells. Thus, this system provides a safe and convenient reporter WNV manipulating tool which can be used to study WNV viral invasion mechanisms, neutralizing antibodies and antiviral efficacy.